2006
DOI: 10.1097/01.mpa.0000220860.01120.21
|View full text |Cite
|
Sign up to set email alerts
|

Defined Localization of Nestin-expressing Cells in l-arginine-induced Acute Pancreatitis

Abstract: Transient nestin expression occurs in specific cell types during the proliferative stage after recovery from L-arginine-induced pancreatitis and may represent the contribution of stem cells and/or progenitor cells to the regenerative capacity of the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…In vivo, Nestin is not present in endocrine cells during either embryogenesis or adulthood, underscoring the conclusion that endocrine cells do not derive from Nestin-expressing progenitors (7,8,(11)(12)(13)(14)(15). Moreover, in rodents, Nestin-expressing cells contribute to the regenerative capacity of the exocrine pancreas after partial pancreatectomy and during recovery from acute pancreatitis (15,16).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In vivo, Nestin is not present in endocrine cells during either embryogenesis or adulthood, underscoring the conclusion that endocrine cells do not derive from Nestin-expressing progenitors (7,8,(11)(12)(13)(14)(15). Moreover, in rodents, Nestin-expressing cells contribute to the regenerative capacity of the exocrine pancreas after partial pancreatectomy and during recovery from acute pancreatitis (15,16).…”
Section: Resultsmentioning
confidence: 76%
“…As shown in (Fig. 1 E-H Inasmuch as Nestin is up-regulated when acinar cell proliferation is induced in the pancreas (15,16) and is expressed in multiple cultured human pancreatic cancer cell lines (present work; data not shown), one could propose that Nestin expression is activated or up-regulated in the pancreas during transformation. Our following in vivo data strongly suggest that the initial oncogenic event occurs in Nestin-expressing cells.…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, the expression of intermediate filament Nestin is regulated by WT1 (93). The expression of Nestin is increased in regenerating tissue and is believed to participate in cellular remodeling and angiogenesis (94)(95)(96). Coexpression of WT1 and Nestin was found in the epicardium and endothelial cells of the embryonic heart in mice (93) and in vascular endothelium of patients who died after MI (97,98).…”
Section: The Role Of Wt1 In Endothelial Cellsmentioning
confidence: 89%
“…16,17,21 Moreover, it has been recently demonstrated that activation of oncogenic K-ras in the nestin cell lineage is sufficient for the initiation of premalignant pancreatic intraepithelial neoplasia (PanIN) lesions in mice. 27 We have recently reported that nestin immunoreactivity was present in the cancer cells in approximately 30% of PDAC cases, and that nestin expression in pancreatic cancer cells correlated with nerve invasion and the presence of cancer cells at the tumor resection margins.…”
Section: Introductionmentioning
confidence: 99%